One Piece. Collection no. 17 [videorecording (DVD)]. (Funimation, 2016)
Luffy turns a mermaid auction into a pirate-style brawl when he knocks the snot out of a celestial dragon. The punch heard round the island may have saved Camie, but it lands the Straw Hats squarely in the sights of the marines! Fellow pirates Trafalgar Law and Eustass Captain Kid buy the crew some time to escape, but the situation gets tricky when an army of Kuma-clone Pacifistas hit the scene.